Effect of Storage Condition and Periods on Seed Germination of Cempaka Wasian (Magnolia tsiampaca (Miq.) Dandy) - Arif Irawan; Hanif Nurul Hidayah (Jurnal Perbenihan Tanaman Hutan, 2019)
Cempaka wasian (Magnolia tsiampaca (Miq.) Dandy) is one of the most popular carpentry woods in North Sulawesi.  The development of cempaka wasian species is constrained by the inability of seeds to be stored for a long period of time. The purpose of this research was to determine the effect of different storage periods and conditions towards seed germination of cempaka wasian. The experimental design used completely randomized factorial design with two main factors as follow: storage condition and storage periods. The results showed that the conditions and storage periods had an effect on seed water content, germination rate, and seed vigor index of cempaka wasian seeds, but it did not affect the germination capacity. The storage conditions of air condition room (temperature 18ºC―21ºC, relative humidity 51percent―61 percent) was the most ideal condition for storing cempaka wasian seeds. Cempaka wasian seeds are included in the category of intermediate seed because the treatment of the storing period for 4 (four) weeks did not affect the germination capacity even though the water content of the seeds has decreased.